Centrosomal protein FOR20 is essential for cilia‐dependent development in zebrafish embryos. Issue 3 (26th November 2018) - Xie, Shanshan; Jin, Juan; Xu, Zhangqi; Huang, Yuliang; Zhang, Wen; Zhao, Lu; Jan Lo, Li; Peng, Jinrong; Liu, Wei; Wang, Fudi; Shu, Qiang; Zhou, Tianhua
ABSTRACT: Centrosomal proteins play critical roles in ciliogenesis. Mutations in many centrosomal proteins have been documented to contribute to developmental defects and cilium‐related diseases. Centrosomal protein fibroblast growth factor receptor 1 oncogene partner–related protein of 20 kDa (FOR20) is crucial for ciliogenesis in mammalian cells and the unicellular eukaryote Paramecium ; however, the biologic significance of FOR20 in vertebrate development remains unclear. We cloned the zebrafish homolog of the for20 gene and found that for20 mRNA is enriched in ciliated tissues during early zebrafish development. Knockdown of for20 by morpholino oligonucleotides in zebrafish results in multiple ciliary phenotypes, including curved body, hydrocephaly, pericardial edema, kidney cysts, and left‐right asymmetry defects. for20 morphants show reduced number and length of cilia in Kupffer's vesicle and pronephric ducts. High‐speed video microscopy reveals that cilia in most for20 morphants are consistently paralyzed or beat arrhythmically. To confirm the ciliary phenotypes of for20 morphants, we used the CRISPR/Cas9 system to disrupt for20 gene in zebrafish. for20 mutants exhibit multiple ciliary phenotypes resembling the defects in for20 morphants. All of these phenotypes in for20 morphants and mutants are significantly reversed by exogenous expression of for20 mRNA. Taken together, these data suggest that FOR20 is required for cilium‐mediated processes during zebrafish embryogenesis.—Xie, S., Jin, J., Xu, Z., Huang, Y., Zhang, W., Zhao, L., Lo, L. J., Peng, J., Liu, W., Wang, F., Shu, Q., Zhou, T. Centrosomal protein FOR20 is essential for cilia‐dependent development in zebrafish embryos. FASEB J. 33, 3613–3622 (2019). www.fasebj.org